Angka Kematian Terkait Anestesi RSUP Dr. Sardjito 2017-2021 - Gunawan, Fanny; Sudadi; Mahmud (Jurnal Komplikasi Anestesi, 2021)
Background: Anesthesia service is a complex part of health care and has the potential to be dangerous. Anesthesia services can be improved by knowing the death rate related to anesthesia. This study aims to determine the death rate related to anesthesia in RSUP Dr. Sardjito. Methods: A retrospective review of the patient database under anesthesia from January 2017 to May 2021 was carried out by taking data from the medical record installation of RSUP Dr. Sardjito. Data on patients who died related to anesthesia were determined by 3 anesthesiologists. We assessed the patient's preoperative, intraoperative, and postoperative variables such as age, sex, ASA physical status, anesthetic technique, type of surgery, size of surgery, and patient comorbidities associated with anesthesia-related death and place of death. Results: There were 39,965 patients undergoing anesthesia. Thirty patients died related to anesthesia. Characteristics of patients who died related to anesthesia in January 2017 to May 2021 at Dr. Sardjito was a patient with male gender (n=14 (46.6%)), ASA III physical status (n=20 (66.7%)), type of emergency surgery (n=12 (40%)), general anesthetic technique (n=25 (83.3%)), and underwent major surgery (n=25 (83.3%)). The mean age of patients who died related to anesthesia was 46.53 with a standard deviation SD of ±26.31. There were 9 patients (30%) who died with comorbid hypertension. There were twenty six patients (86.6%) died outside the operating room. Conclusion: The death rate related to anesthesia within 24 hours at RSUP Dr. Sardjito is 7.5 per 10,000 anesthetic actions.